Assessment of salinity tolerance in onion (Allium cepa L.) genotypes at germination stage through morphological traits and multivariate analysis - Kasar, Shreya; Roylawar, Praveen; Furtado, Bliss; Khandagale, Kiran; Nanda, Satyabrata; Bhandari, Snehal; Khyade, Mahendra; Gedam, Pranjali; Bhandari, Hem Raj; Mahajan, Vijay; Gawande, Suresh (Frontiers in Plant Science, 2026)
Salinity is a major abiotic stress that affects crop growth and development, particularly in crops like onions (Allium cepa L.), which are sensitive to saline conditions. Salinity stress limits crop productivity and is difficult to simulate on farms, hindering parental selection for hybridization programs and the development of tolerant cultivars. In this study, 116 A. cepa genotypes and released varieties with different genetic backgrounds were used to develop and validate a reliable screening method for salinity tolerance in onion genotypes at early growth stages. The study was conducted in 2 phases. The first was to determine the optimum salt concentration for screening salinity tolerance, and the second was to determine salinity tolerant genotypes and a reliable screening trait for salinity tolerance at the germination/seedling stage. An optimum concentration of 150 mM NaCl, thus found, was used to assess the salinity tolerance of other 100 genotypes by observing key morphological parameters such as germination rate (GR), shoot length (SL), root length (RL), shoot fresh weight (SFW), root fresh weight (RFW), and total fresh weight (TFW). With the help of mean membership function value, and a mathematical model evaluation criteria, the 100 genotypes were categorized into five grades: 6 Highly Salinity Tolerant, 12 Salinity -Tolerant, 59 Moderately Salinity Tolerant, 10 Salinity -Sensitive, and 13 ungerminated genotypes were classified Highly Salinity -Sensitive. Principal Component Analysis was performed to identify key traits contributing to salinity tolerance in A. cepa for effective genotype selection. Total fresh weight at 150 mM NaCl was found to be an ideal trait, demonstrating the extent to which A. cepa genotypes respond to saline conditions. The methodology within this study presents a simple, efficient, and replicable model for the evaluation of salinity tolerance at germination of onion and other cultivars of economic importance.